2016
DOI: 10.1371/journal.pone.0163699
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Plasma Levels of MicroRNA-21 and MicroRNA-221 Are Potential Diagnostic Markers for Primary Intrahepatic Cholangiocarcinoma

Abstract: BackgroundMicroRNAs (miRNAs) are potential biomarkers in various malignancies. We aim to characterize miRNA expression in intrahepatic cholangiocarcinoma (ICC) and identify circulating plasma miRNAs with potential diagnostic and prognostic utility.MethodsUsing deep-sequencing techniques, miRNA expression between tumor samples and non-neoplastic liver parenchyma were compared. Overexpressed miRNAs were measured in plasma from an independent cohort of patients with cholangiocarcinoma using RT-qPCR and compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 58 publications
0
52
0
Order By: Relevance
“…Furthermore, miRNAs can be easily detected in small amounts and are resistant to degradation (20,22). These characteristics make miRNAs attractive as potential biomarkers (20). In the present study it was determined that data showed that plasma miR-142-5p was significantly increased in patients with ICC compared with healthy controls.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, miRNAs can be easily detected in small amounts and are resistant to degradation (20,22). These characteristics make miRNAs attractive as potential biomarkers (20). In the present study it was determined that data showed that plasma miR-142-5p was significantly increased in patients with ICC compared with healthy controls.…”
Section: Discussionmentioning
confidence: 59%
“…It is important to detect ICC early in order to improve treatment outcomes. Increasing evidence has suggested that miRNAs may be used as potential diagnostic biomarkers for ICC and may also serve as therapeutic targets (19,20). miRNAs are able to stably exist in bodily fluids, including serum, plasma, saliva, urine and tears (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the use of miRNAs for early detection of CCA, only a few studies of sufficient quality exist to date. In a small cohort of patients, serum levels of miR-21 and miR-221 were found to be significantly elevated in patients with intrahepatic CCA compared to healthy controls (AUC = 0.94) [27]. These findings were corroborated by a different study, showing that circulating levels of miR-21 are able to differentiate between CCA patients and healthy controls (AUC = 0.93) as well as patients with nonmalignant bile duct disease (AUC = 0.83) and decrease after tumor resection [28].…”
Section: Resultsmentioning
confidence: 99%